2022
DOI: 10.1007/s10750-022-04843-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting effects of experimental flow intermittency on alpine stream macroinvertebrates (Val Roseg, Switzerland)

Abstract: Changing weather patterns and receding glaciers are predicted to increase flow intermittency in alpine streams. If aquatic macroinvertebrate communities largely comprise taxa adapted to perennial flows, an increase in flow intermittency substantially reduces biodiversity and affects functional processes. We conducted a before-after-control-impact field experiment to examine how macroinvertebrate communities in an alpine headwater stream responded to and recovered from a repeated experimental increase in flow i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 76 publications
(119 reference statements)
0
3
0
Order By: Relevance
“…This implies that recolonisation rates were high in this catchment, probably as a result of high ecological connectivity (Leys et al, 2016;Siebers et al, 2019). However, previous studies have also shown that when summer drying events occur in alpine streams that used to flow throughout the season, macroinvertebrate densities and richness are greatly reduced and assemblages are slow to recover (Drost et al, 2022;Piano et al, 2019;Siebers et al, 2020).…”
Section: Perspectives and Implicationsmentioning
confidence: 80%
See 2 more Smart Citations
“…This implies that recolonisation rates were high in this catchment, probably as a result of high ecological connectivity (Leys et al, 2016;Siebers et al, 2019). However, previous studies have also shown that when summer drying events occur in alpine streams that used to flow throughout the season, macroinvertebrate densities and richness are greatly reduced and assemblages are slow to recover (Drost et al, 2022;Piano et al, 2019;Siebers et al, 2020).…”
Section: Perspectives and Implicationsmentioning
confidence: 80%
“…This implies that recolonisation rates were high in this catchment, probably as a result of high ecological connectivity (Leys et al, 2016; Siebers et al, 2019). However, previous studies have also shown that when summer drying events occur in alpine streams that used to flow throughout the season, macroinvertebrate densities and richness are greatly reduced and assemblages are slow to recover (Drost et al, 2022; Piano et al, 2019; Siebers et al, 2020). Assemblages in Val Roseg may therefore be adapted to the current prevalence of flow intermittency at a network scale given that flow intermittency has been widespread across the valley for—at the very least—over a decade (Robinson, Thompson, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation